The impact of lithology in the recharge area on the hydrochemical properties of the Slatinski Izvor spring (North Macedonia) - Gichevski, Biljana; Hristovski, Slavčo (Macedonian Journal of Ecology and Environment, 2024)
The Slatinski Izvor spring is located in the Poreče basin, in the Slatinska Reka river valley in the central part of the Treska river basin. Hydrochemical characteristics of water from the karst spring Slatinski Izvor were analysed in the period between June 2013 and June 2014. The results showed that the lithology of the catchment area of the spring is reflected in the chemical composition of the water. All used methods showed that spring belongs to calcium bicarbonate water type. The spring had typical shallow and fresh water and short residence time of the water in the karst aquifer. All water samples had low concentration of nutrients and heavy metals and can be considered as potential for water supply and irrigation.